-x-3=-3x+3

Simple and best practice solution for -x-3=-3x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-3=-3x+3 equation:


-x-3=-3x+3

We simplify the equation to the form, which is simple to understand
-x-3=-3x+3

We move all terms containing x to the left and all other terms to the right.
-1x+3x=+3+3

We simplify left and right side of the equation.
+2x=+6

We divide both sides of the equation by 2 to get x.
x=3

See similar equations:

| 5y^2+4-12=0 | | 5.2=4x-1.2 | | (x-5-7i)(x-5+7i)=0 | | 2x-3+12x=15+7x-4 | | y=2x+55 | | 12+2x=-18 | | 108=12(X+3) | | y/5-3.4=-15.9 | | 2x^3-5x^2+40x-100=0 | | 2x+5.5y=17 | | -6+x=6-3x | | 12a-14=8 | | (2y-6)+y=180 | | 81x^4=3x | | -7-z=12-z | | a=1+8*2+(8-4)*7 | | 4x(3x)+5-7=56 | | -3x+7=5-4x | | -6x-13=-61 | | 9=5+9b | | 6l+3l=5.4 | | sin(5x)=3sin(3x) | | 8-9x=21x-7 | | y=f(-x) | | 2x-13=12-3x | | 6a-2b=32 | | -8-9x=21-7 | | y=f(x)-8 | | -1.8=-.6 | | 9(t-8)/4 | | (4y-9)(5-y)=0 | | -3-x=4-2x |

Equations solver categories